Da razão prática kantiana à teoria da justiça rawlsiana : os pressupostos morais do liberalismo político - Orben, Douglas João (2019)
The scope of philosophical discussions about ethics, morality, politics, and justice is radically impacted by the ideas of John Rawls (1921-2002). In A Theory of Justice (1971), the American philosopher exposes his constructivist conception of justice as fairness, which is admittedly inspired and grounded in Kant's practical reason (1724-1804). Nevertheless, the Rawlsian intellectual itinerary undergoes profound changes, so that in Political Liberalism (1993) a strictly political conception of justice is presented. In effect, the principles of political liberalism are exposed as freestanding, with no link to Kantian moral presuppositions or even to any other philosophical doctrine. This would be a necessary condition for an overlapping consensus between the different conceptions of good existing in democratic societies. In this context, the present research questions the idea of freestanding of the political scope, seeking to highlight some moral assumptions not explicitly stated by Rawls. In the light of a semantic agreement that differentiates the scopes of application of ethics, politics, and moral, this discussion intends to demonstrate that there is a moral foundation in political liberalism, which, however, should not be understood in the ethical sense. This moral assumption would be in Kantian practical reason, for it is from this that Rawls sets out to structure and ground his conception of justice. Hence, the principles of Rawlsian political liberalism, in order to be effective when applied to the basic structure of society, must be analyzed through the moral elements of Kantian practical reason. Finally, this research seeks to show that such moral presupposition puts the idea of freestanding of the political scope in check, however, does not compromise the possibility of an overlapping consensus nor the establishment of the priority of the right over the good. That‘s because Kantian morality, unlike ethical conceptions of good, meets the criteria of objectivity and publicity required by the political scope.